Estudo do metabolismo de zinco em plantas de milho transgênico submetidas ao herbicida glifosato utilizando técnicas analíticas nucleares - Wellington Ferrari da Silva (2019)
Maize cultivation has undergone major technological advances in recent years, especially since glyphosate-tolerant cultivars have emerged on the market. The use of this herbicide aims at eliminating the weeds present in the crops, but this product may influence the growth and mineral nutrition of the plants. The objective of this research was to evaluate the effect of the application of glyphosate under agronomic point of view and the effect in the absorption and translocation of zinc in the product tolerant corn. Three experiments were carried out: Experiment 1, cultivation in hydroponics, conducted in a factorial scheme (3 x 2), with three replications, with two plants per treatment. Treatments consisted of 3 doses of the herbicide glyphosate (control, recommended dose, 4 times the recommended dose). Experiment 2, soil cultivation, was conducted in a factorial scheme (3 x 3), with two replications, with two plants per treatment. The treatments consisted of the same dosage of glyphosate herbicide from the previous experiment and with 3 doses of zinc (0 mg kg-1, 5 mg kg-1and 10 mg kg-1 ZnSO4). Experiment 3, cultivation in hydroponics with radioactive tracer 65Zn was performed in a factorial scheme (3 x 1), with one replicate, with three plants per treatment. Treatments consisted again of the same doses of the herbicide glyphosate and a dose of radioactive zinc, 65Zn (0.22 g L-1). The plants were harvested and separated in root, stem, central, medium and low leaves. The analytical technique used to quantify the zinc in experiments 1 and 2 was the neutron activation analysis, standardized k0 method, irradiating the samples in the TRIGA MARK I IPR-R1 nuclear research reactor of the Nuclear Technology Development Center / Brazilian Commission for Nuclear Energy (CDTN / CNEN). The total activity of 65Zn was determined by gamma spectrometry analysis. The results of this research suggest that the dosage application higher than the recommended dosage of the herbicide glyphosate interfered in almost all parameters evaluated. The application of the recommended dose in the cultivation in hydroponics, negatively affected the translocation of zinc and the dry matter of the stem and shoot. Related to experiment in soil cultivation, the application of the recommended dose of glyphosate was satisfactory, in other words, the growth of the plant and the absorption and translocation of zinc were not affected.